Social Networks of Moravian Benedictine Monasteries in the Premyslid Period (Part I The Olomouc Hradisko) - Šrámek, Josef (Historica Olomucensia, 2021)
The rise of new Cistercian and Premonstratensian monastic orders in the twelfth century is a traditional theme of global medieval studies. The Czech discourse proposes that the new movements could only blossom because Benedictine monasticism had bled out internally and was unable to step up to the challenges of the new era. Such generalizations however lack the support of specific data, which makes us question the conclusion as being possibly too schematic. The reasons leading to the new monastery were varied, from pastoral, mortuary, and generally commemorative incentives, through representational factors, to economic and political aspects. Although the arrival of the Cistercians and Premonstratensian meant the end of a certain hegemony of the Benedictines, the monasteries did not disappear and new ones, if fewer, were built well into the fourteenth century in the Czech lands. The study focuses on Moravian Benedictine monasteries in the Přemyslid era (until the end of the thirteenth century). It illustrates, based on the oldest Benedictine house - the Hradisko Abbey near Olomouc, the social networks in which these religious houses were perched, and shows relationships the institutions maintained and the role they played in contemporary society.
Keywords: Middle Ages; Ecclesiastical History; Monasticism; Benedictines; Social Networks; Moravia; Olomouc Hradisko